Consumption of Hibiscus sabdariffa L. aqueous extract and its impact on systemic antioxidant potential in healthy subjects - Frank, Thomas; Netzel, Gabriele; Kammerer, Dietmar R; Carle, Reinhold; Kler, Adolf; Kriesl, Erwin; Bitsch, Irmgard; Bitsch, Roland; Netzel, Michael (Journal of the science of food and agriculture, 2012)
BACKGROUND: To evaluate health benefits attributed to Hibiscus sabdariffa L. a randomized, open‐label, two‐way crossover study was undertaken to compare the impact of an aqueous H. sabdariffa L. extract (HSE) on the systemic antioxidant potential (AOP; assayed by ferric reducing antioxidant power (FRAP)) with a reference treatment (water) in eight healthy volunteers. The biokinetic variables were the areas under the curve (AUC) of plasma FRAP, ascorbic acid and urate that are above the pre‐dose concentration, and the amounts excreted into urine within 24 h (Ae0–24) of antioxidants as assayed by FRAP, ascorbic acid, uric acid, malondialdehyde (biomarker for oxidative stress), and hippuric acid (metabolite and potential biomarker for total polyphenol intake). RESULTS: HSE caused significantly higher plasma AUC of FRAP, an increase in Ae0–24 of FRAP, ascorbic acid and hippuric acid, whereas malondialdehyde excretion was reduced. Furthermore, the main hibiscus anthocyanins as well as one glucuronide conjugate could be quantified in the volunteers' urine (0.02% of the administered dose). CONCLUSION: The aqueous HSE investigated in this study enhanced the systemic AOP and reduced the oxidative stress in humans. Furthermore, the increased urinary hippuric acid excretion after HSE consumption indicates a high biotransformation of the ingested HSE polyphenols, most likely caused by the colonic microbiota. Copyright © 2012 Society of Chemical Industry